Theravāda Buddhist Abhidhamma and Moral Development: Lists and Narratives in the Practice of Religious Ethics - Clairmont, David A. (Journal of the Society of Christian Ethics, 2010)
THIS ESSAY EXAMINES THE RELEVANCE FOR RELIGIOUS ETHICS OF BUDDHIST Abhidhamma texts, those dealing with the analysis and systematization of mental states arising in and examined by meditation practice. Developing recent scholarship on the prevalence and significance of interlocking lists in Buddhist canonical texts and commentaries, the Buddhist use of lists in the Abhidhamma constitutes a kind of narrative expression of moral development through the sequential occurrence of carefully defined mental states. Attention to this narrative dimension of the moral life, while related to other recent proposals about the place of narrative in religious ethics, offers a way to employ this underexamined genre of religious literature (lists) drawn from a comparative context (Buddhist and Christian ethics), in service of a more nuanced account of moral development.